SOCS5 Is Expressed in Primary B and T Lymphoid Cells but Is Dispensable for Lymphocyte Production and Function - Brender, Christine (American Society for Microbiology, 2004)
Suppressors of cytokine signaling (SOCSs) are key regulators of cytokine-induced responses in hematopoietic as well as nonhematopoietic cells. SOCS1 and SOCS3 have been shown to modulate T-cell responses, whereas the roles of other SOCS family members in the regulation of lymphocyte function are less clear. Here, we report the generation of mice with a targeted disruption of the Socs5 gene. Socs5(−/−) mice were born in a normal Mendelian ratio and were healthy and fertile. We found that SOCS5 is expressed in primary B and T cells in wild-type mice. However, no abnormalities in the lymphocyte compartment were seen in SOCS5-deficient mice. We examined antigen- and cytokine-induced proliferative responses in B and T cells in the absence of SOCS5 and found no deviations from the responses seen in wild-type cells. Because SOCS5 has been implicated in Th1 differentiation, we also investigated the importance of SOCS5 in T helper cell responses. Unexpectedly, SOCS5-deficient CD4 T cells showed no abnormalities in Th1/Th2 differentiation and Socs5(−/−) mice showed normal resistance to infection with Leishmania major. Therefore, although SOCS5 is expressed in primary B and T cells, it appears to be dispensable for the regulation of lymphocyte function.